2017
DOI: 10.1002/cepa.493
|View full text |Cite
|
Sign up to set email alerts
|

17.06: Characterization of accidental scenarios for offshore structures

Abstract: Offshore structures are complex facilities whose malfunction can lead to serious impacts and losses, such as human lives, environmental disasters and the complete loss of the structure. Additionally, the cost associated to their construction and maintenance is very high, so it is crucial to keep them fully operational throughout their entire service life. Standby periods in offshore platforms generate large financial losses for their owners. The most devastating effects on offshore platforms are often the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…According to the definition, "major accident" means "an adverse phenomenon, such as major emissions, fire or explosion". These accidents resulting from uncontrolled events during the operation of an objective covered by the presence of the Seveso Directives and which poses a serious danger to human health and / or the environment, immediately or late, inside or outside the target, involving one or more hazardous substances" [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…According to the definition, "major accident" means "an adverse phenomenon, such as major emissions, fire or explosion". These accidents resulting from uncontrolled events during the operation of an objective covered by the presence of the Seveso Directives and which poses a serious danger to human health and / or the environment, immediately or late, inside or outside the target, involving one or more hazardous substances" [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, for example, blast-resistant walls are usually made of steel and/or reinforced concrete, or can be made of prefabricated slabs. Furthermore, explosion-proof walls isolate nonhazardous areas and therefore minimize the effects of explosive charges [6].…”
Section: Introductionmentioning
confidence: 99%
“…An overview of blast mitigation measures for offshore structures was presented in [4]. It was shown that, for offshore structures, for example, blast walls are usually made of steel and provide a barrier that protects a muster area from the blast impact.…”
Section: Introductionmentioning
confidence: 99%